2008
DOI: 10.1063/1.2949404
|View full text |Cite
|
Sign up to set email alerts
|

Deformation pathway to high-pressure phases of silicon during nanoindentation

Abstract: The deformation pathway of silicon induced by nanoindentation is investigated in detail at the atomic level using molecular dynamics. Due to the complex stresses associated with the directional loading along a specific crystallographic orientation, the initial Si I lattice is transformed into two different high-pressure phases, namely, Si II and BCT5-Si. The Si II phase, where atoms have the six nearest neighbors, is generated through the tetragonal deformation caused by the compressive loading along the [001]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 51 publications
2
28
0
Order By: Relevance
“…2) Consequently, we obtained the complete scenario of structural changes induced in Si crystal directly under the diamond tip (Fig. 2), which agrees with previous achievements [22][23][24][26][27][28][30][31][32] and vindicates our MD-procedure with the Tersoff-type potential.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…2) Consequently, we obtained the complete scenario of structural changes induced in Si crystal directly under the diamond tip (Fig. 2), which agrees with previous achievements [22][23][24][26][27][28][30][31][32] and vindicates our MD-procedure with the Tersoff-type potential.…”
supporting
confidence: 78%
“…The interactions among Si atoms were defined by the three-body Tersoff-type interatomic potential [21] capable of capturing phase transformations between crystalline silicon structures [19,[22][23][24][26][27][28]. The interaction between the Si-crystal and a rigid, diamond, cono-spherical tip (the half apex angle of π/4, radius of R=5 nm) was defined by the repulsive Morse potential (cutoff radius 3 Å).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations on the mechanical properties and deformation mechanism of silicon indicated the appearance of the metastable phases, Si-II, Si-XII, and amorphous phase during nanoindentation process. Whilst, several simulated results showed that the Si-I transformed into two types of body-centered-tetragonal phase, i.e., β-Si and Bct5 with fivefold coordination [4,22,23]. The abrasive wear of monocrystalline silicon showed a new phase transformation route, i.e., an initial diamond cubic silicon turned into high density amorphous phase beneath the moving particle and, then transformed into low density metastable amorphous phase in both two-body and three-body abrasion [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Fang et al [18] assumed an ellipsoidal particle as the first approximation to model real particle contours in three-body abrasion. In addition, much effort has been paid for the abrasion properties of monocrystalline silicon at nanoscale by the molecular dynamics (MD) simulation [19][20][21][22][23]. For instance, Sun et al [24,25] simulated three-body and two-body abrasive wear of monocrystalline silicon with sphere particle in geometry in the nanoscale.…”
Section: Introductionmentioning
confidence: 99%